"Volkskapitalisme" in the transition to democracy and beyond. Issue 1 (2nd January 2019) - Padayachee, Vishnu; Rossouw, Jannie
ABSTRACT: In an assessment of the transition of the Afrikaans business sector to the post-democracy period in South Africa since 1994, the growth or the PSG Group since 1995 is remarkable. We use a biography or Jannie Mouton, the founder and Chairperson of PSG, as a basis for this analysis. His story is quintessentially a narrative of Afrikaner business adjustment in the new democratic South Africa. The success of PSG after democratic elections in 1994 shows some similarities to other Afrikaner business interests developed in the period between the First and Second World Wars. This business development was not overly dependent on the state and can be viewed as a form of "volkskapitalisme". In contract, the ANC government has taken an active role in attempts to develop black business in South Africa through a policy of black economic empowerment (BEE). The assessment of the success of the PSG Group under the leadership of Mouton shows that the company developed the ability to identify and use opportunities for growth. This ability makes Mouton arguably the most influential South African businessman (black or white) of this current generation. Mouton's personal success and the success of the PSG Group serve as an example for South Africans.